Insufficient info, maybe?

Algebra Level 4

Two real numbers x x and y y are such that x + y 0 x+y \ne 0 . Find the minimum value of

x 2 + y 2 + ( 1 + x y x + y ) 2 \large x^2+ y^2+\left(\frac {1+xy}{x+y}\right)^2

Write your answer to 2 decimal places.


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

James Wilson
Oct 24, 2017

I took the partial derivatives w.r.t x x and y y , and set them equal to 0 0 . Skipping some steps, this resulted in the equations x ( x + y ) 3 + ( 1 + x y ) ( y 2 1 ) = 0 x(x+y)^3+(1+xy)(y^2-1)=0 y ( x + y ) 3 + ( 1 + x y ) ( x 2 1 ) = 0. y(x+y)^3+(1+xy)(x^2-1)=0. Subtracting them results in ( x y ) ( x 2 + x y + y 2 1 ) = 0 (x-y)(x^2+xy+y^2-1)=0 . If we let x y = 0 x-y=0 , then using either condition results in x 2 = 1 3 x^2=\frac{1}{3} . Substituting it into the expression (to be minimized), one obtains 2 x 2 + ( 1 + x 2 ) 2 4 x 2 = 2 3 + 16 9 4 3 = 2. 2x^2+\frac{(1+x^2)^2}{4x^2}=\frac{2}{3}+\frac{\frac{16}{9}}{\frac{4}{3}}=2. If we let x 2 + x y + y 2 1 = 0 x^2+xy+y^2-1=0 , then we can substitute 1 x y 1-xy for x 2 + y 2 x^2+y^2 anywhere it occurs in the expression (to be minimized), obtaining x 2 + y 2 + ( 1 + x y ) 2 x 2 + y 2 + 2 x y = 1 x y + ( 1 + x y ) 2 1 x y + 2 x y = 1 x y + ( 1 + x y ) 2 1 + x y = 1 x y + 1 + x y = 2. x^2+y^2+\frac{(1+xy)^2}{x^2+y^2+2xy}=1-xy+\frac{(1+xy)^2}{1-xy+2xy}=1-xy+\frac{(1+xy)^2}{1+xy}=1-xy+1+xy=2. So, therefore, since the expression is strictly positive, with only one discontinuity, an infinite discontinuity, we can see that the global minimum is 2 2 .

Matteo Di Prinzio
Jul 29, 2019

From the inequality

( x + y 1 + x y x + y ) 2 > 0 (x+y-\frac{1+xy}{x+y})^{2}>0

one gets

x 2 + y 2 + ( 1 + x y x + y ) 2 > 2 ( x + y ) 1 + x y x + y 2 x y = 2 x^2+y^2+(\frac{1+xy}{x+y})^2>2(x+y)\frac{1+xy}{x+y}-2xy = 2

By letting x = 1 , y = 0 x=1, y=0 in x 2 + y 2 + ( 1 + x y x + y ) 2 x^2+y^2+(\frac{1+xy}{x+y})^2 One can see that "2" is the solution

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...